Mastering computer typing - Lindsell-Roberts, Sheryl (Houghton Mifflin Harcourt, 2010)
Updated with new exercises and material on e-mail, instant messaging and other business communications outlines a 24-hour program for learning to type quickly and accurately without looking at a keyboard, sharing additional exercises for understanding etiquette and avoiding discomfort.